Students' Mathematical Communication Skills in Solving Quadratic Equation Problems - Reza Muhamad Zaenal; Tio Heriyana (Lembaga Intelektual Muda (LIM) Maluku, 2021)
Mathematics learning today only emphasizes the mastery of the material alone and more one-way communication with students. The buildup of information from teachers results in the learning style of students who tend to memorize. This research aims to find out the mathematical communication skills of students in solving quadratic equation problems. This type of research is qualitative descriptive. Determination of the subject using purposive sampling techniques with the criteria of the student's test results. The study subjects numbered three people consisting of students who obtained grades in high, medium, and low categories. Indicators of communication skills in this researcher are (1) explain and make mathematical statements that have been studied, (2) state everyday events in a language or mathematical symbol, and (3) provide an explanation of mathematical ideas, concepts, or situations with their own language in the form of writing mathematically. The instruments used are researchers, tests and interviews. Data analysis techniques are using quantitataif data analysis with data reduction stages, data presentation, and conclusion withdrawal. The results of the data analysis showed that the KSS subject met 3 indicators of mathematical communication skills. AHB subjects meet 2 of the 3 indicators, namely the first and third indicators. WL subjects meet reached 1 of 3 indicators of mathematical communication skills, namely the first indicators.